2018
DOI: 10.1002/ijch.201700034
|View full text |Cite
|
Sign up to set email alerts
|

Transition Metal‐Catalyzed Benzannulation towards Naturally Occurring Carbazole Alkaloids

Abstract: In this account, we will summarize our recent progress on development of Pt‐ or Au‐catalyzed benzannulation of 1‐indolyl‐2,3‐allenols for the efficient construction of carbazole skeleton via a metal carbene intermediate and its application towards the synthesis of naturally occurring carbazole alkaloids. The strategy enjoys the outstanding regioselectivity, atom economy, mild reaction conditions, substrate scope, functional group tolerance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…Along with that, as mentioned earlier, the limitations are also overcome by the typical use of Rh-benzannulation protocols . The benzannulation term was originally adopted from the Latin word indicating the formation of two new bonds in the rapid “anellus method” . Gratifyingly, Rh-catalyzed benzannulations are promising and scalable techniques in modern organic synthesis pursuits in which new rings are formed over a pre-existing scaffold efficiently. Additionally, Rh-catalyzed pathways are also known to foster many benefits, including no requirement of prefunctionalization, chemodivergent–convergent pathway, and straightforward and rapid access to molecular complexity in a one-shot manner.…”
Section: Introductionmentioning
confidence: 99%
“…Along with that, as mentioned earlier, the limitations are also overcome by the typical use of Rh-benzannulation protocols . The benzannulation term was originally adopted from the Latin word indicating the formation of two new bonds in the rapid “anellus method” . Gratifyingly, Rh-catalyzed benzannulations are promising and scalable techniques in modern organic synthesis pursuits in which new rings are formed over a pre-existing scaffold efficiently. Additionally, Rh-catalyzed pathways are also known to foster many benefits, including no requirement of prefunctionalization, chemodivergent–convergent pathway, and straightforward and rapid access to molecular complexity in a one-shot manner.…”
Section: Introductionmentioning
confidence: 99%
“…In 1987, the first homogeneous gold-catalyzed addition of nucleophiles to alkynes was realized by the group of Utimoto using sodium tetrachloroaurate dihydrate. , One decade later, Teles et al and Tanaka et al demonstrated the possibility of activating alkynes using gold­(I) complexes. From that point, the field of gold­(I) catalysis started to gain momentum year after year and still today remains one of the most active areas of research in organometallic chemistry. , This comes as a consequence of the ability of gold­(I) complexes to activate π bonds in a very selective manner. Its potential, attributed partially to relativistic effects, is illustrated by the wide molecular complexity that can be built through the gold­(I)-catalyzed cycloisomerization of enynes (Scheme ). …”
Section: Introductionmentioning
confidence: 99%
“…The assembly of the core structures of such compounds are often achieved by organic transformations of these enones (Figure ). Remote functionalization, particularly at the γ-positions of dienolates and ε-positions of trienolates, is rather inefficient due to the reduced nucleophilicity at these positions when compared to α-enolates …”
mentioning
confidence: 99%